1994
DOI: 10.1099/00222615-40-6-408
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of delayed post-operative endophthalmitis by polymerase chain reaction of bacterial DNA in vitreous samples

Abstract: Delayed post-operative endophthalmitis is a complication of modern cataract extraction and posterior chamber lens implantation. Propionibacterium acnes has been isolated in a few such cases but the majority are culture-negative, compounding surgical and medical management decisions. A method of detecting bacterial, and specifically P. acnes, DNA by the polymerase chain reaction (PCR) directed at 16S rDNA is reported. Nested PCR with universal eubacterial primers complimentary to regions of 16S rDNA conserved s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 28 publications
4
58
0
2
Order By: Relevance
“…Utilizing the nested PCR technique with universal primers and a combination of species-specific primers for Propionibacterium acnes, the method was capable of detecting bacterial DNA in 17 (74%) of 23 specimens of vitreous humor, while the culture was positive in 10 (43.5%) of these specimens. Bacterial DNA was detected by PCR in 8 specimens with a negative culture and in all cases where there was bacterial growth in culture (18) .…”
Section: Molecular Detection and Identification In Cases Of Bacterialmentioning
confidence: 99%
“…Utilizing the nested PCR technique with universal primers and a combination of species-specific primers for Propionibacterium acnes, the method was capable of detecting bacterial DNA in 17 (74%) of 23 specimens of vitreous humor, while the culture was positive in 10 (43.5%) of these specimens. Bacterial DNA was detected by PCR in 8 specimens with a negative culture and in all cases where there was bacterial growth in culture (18) .…”
Section: Molecular Detection and Identification In Cases Of Bacterialmentioning
confidence: 99%
“…Sampling was conducted under the sterile operating conditions. Viterous aspiration was done slowly using a sterile syringe [17,18]. The specimens were collected in pre-sterilized microfuge tubes and stored at -20˚C for further analysis.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Bacterial 16S rRNA gene was amplified from genomic DNA isolated from the vitreous samples using PCR with a pair of HAD2 universal primers [18,19]: F 5' ACTCCTACGGGAGGCAGCAGT 3' and R 5'GTATTACCGCGGCTGCTGGCA 3'. The PCR reactions were carried out in a total volume of 25 µl containing 2.5 µl of 10× PCR buffer (CinnaGene, Iran), 25 mM MgCl 2 , 10 mM of dNTP, 2 µl of DNA template (50-500 ng) , 0.1µM of each primer, 1.0 U of Taq DNA polymerase.…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…Should subsequent microbiological cultures prove to be negative, this still does not rule out an infectious aetiology as a significant percentage of infectious cases are not bacteriologically identified by using conventional culture techniques. [12][13][14] One recent study showed that by using the polymerase chain reaction in the diagnosis of bacterial endophthalmitis, 54.8% more samples were positive for bacteria compared to conventional culture methods. 14 Both culture negative and culture positive cases were therefore included in the data analysis for this study.…”
Section: Case Definitionmentioning
confidence: 99%